2005
DOI: 10.1061/(asce)0733-9372(2005)131:12(1649)
|View full text |Cite
|
Sign up to set email alerts
|

Regular Transient Loading Response in a Vapor-Phase Flow-Direction-Switching Biofilter

Abstract: Abstract:The principal objective of this study was determination of the response of a laboratory-scale vapor-phase flow-directionswitching biofilter to loading changes associated with normal operations such as lunch breaks, overnight shutdowns, and single-shift operation of commercial and industrial facilities. Three regular transient loading cases were considered: ͑a͒ variable flow-reversal interval lenghts, ͑b͒ variable feed-on/off interval lengths, and ͑c͒ variable inlet concentration during a repeating fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…The change from continuous loading (step B0) to intermittent loading with overnight and weekend starvations (step B1) resulted in an improvement on the RE of the first quarter of the biofilter up to an average value of 90%, indicating that short shut-down periods at moderate operational conditions could help to improve the activated biological system. This observation was previously reported by [14], who concluded that regular transient-loading conditions a microbial population that can better respond to transient loadings than biofilters that are not subject to regular transient loading.…”
Section: Biofilter's Performancesupporting
confidence: 75%
See 2 more Smart Citations
“…The change from continuous loading (step B0) to intermittent loading with overnight and weekend starvations (step B1) resulted in an improvement on the RE of the first quarter of the biofilter up to an average value of 90%, indicating that short shut-down periods at moderate operational conditions could help to improve the activated biological system. This observation was previously reported by [14], who concluded that regular transient-loading conditions a microbial population that can better respond to transient loadings than biofilters that are not subject to regular transient loading.…”
Section: Biofilter's Performancesupporting
confidence: 75%
“…Total biofilter response was excellent for all cases and the impact of transient peaks on biofilter response was apparent only in the inlet region of the bed, indicating the importance of having excess bed depth to assimilate transient changes as Wright et al [14] have pointed out.…”
Section: Response Of the Biofilter To Shock Conditionsmentioning
confidence: 86%
See 1 more Smart Citation
“…In terms of the aromatic compounds, greater degradation occurred in the first half of the bioreactor, with a greater emission of m-xylene, a less biodegradable compound than toluene. The increase in the RE of aromatic compounds halfway down both biofilters after the first three weeks of intermittent loading operations (stage II) in comparison with the end of stage I (day 30), demonstrates that short-term starvation periods related to night and weekend shutdowns under moderate operational conditions, could help to improve the activity of the biological system (Wright et al, 2005). For example, the toluene REs at the first quarter in the P biofilter were 23 and 57% on days 30 (end of stage I) and 50 (stage II) respectively, and in the P-GTR biofilter were 58 and 81% respectively.…”
Section: Compound Degradationmentioning
confidence: 96%
“…As can be seen, results obtained from the pilot-scale unit match those from the laboratoryscale experiments. The slightly better performance of the pilot unit versus the lab-scale BTF may be due to the following: (1) the oxygenated compound composition tested in the pilotscale industrial emission (> 70%) was higher than that tested in the laboratory-scale BTF unit (50%); (2) greater variability in the organic composition of the industrial emission could have derived from a more complex microbial ecosystem; and (3) the short-term starvation periods due to weekend closures at moderate operational conditions could help to improve the activity of the biological system (Wright et al, 2005). Importantly, comparison between the laboratory-scale and pilot-scale units indicate that laboratory studies could be a timesaving tool for obtaining valuable data for scale-up.…”
Section: Comparison With Laboratory-scale Biotechnologiesmentioning
confidence: 99%